6. KNOWLEDGE OF ACUTE STROKE AMONG CAREGIVERS AND ASSOCIATED FACTORS AT THE NATIONAL GERIATRIC HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge regarding acute stroke and related factors among caregivers of stroke patients at the National Geriatric Hospital, 2025.Research methods: A cross-sectional descriptive study was conducted from January to June 2025. A sample of 309 caregivers of patients with acute stroke was gathered. A standardized questionnaire adapted from the Stroke Knowledge Test which comprises 20 multiple-choice questions is used and scores converted to a 100-point scale. Data was analyzed using SPSS version 20.0, employing descriptive statistics.Results and conclusions: The results showed that 69.3% of caregivers had adequate knowledge regarding acute stroke. Basic knowledge items such as causes of stroke (98.7%), warning signs (90%), and the appropriate time to seek emergency care (98.4%) were well recognized. However, awareness of more specialized aspects - such as the association between atrial fibrillation and stroke, or the role of Aspirin in stroke management - remained limited. Several factors were found to be significantly associated with knowledge level, including educational attainment, personal history of illness, relationship to the patient, and sources of information from healthcare providers, printed materials, and family or friends (p < 0.05).
Keywords: Knowledge; acute stroke; caregivers of stroke patients.